Functional field protocol to optimize the choice of footwear on synthetic turf in rugby - Blanchard, S.; Behr, M. (Science & Sports, 2021)
Objectives To avoid injuries and keep up their performances, rugby players have to make relevant choices of footwear adapted to their individual specificities as well as to the type of turf and playing conditions. The diversity and heterogeneity of playing surfaces on which modern rugby is played make this choice all the more complicated. This study examines the relevance of a comparative functional protocol for a subjective assessment of footwear as well as the influence of the technical characteristics of different shoe models.